Tumor growth and angiogenesis are dependent on the presence of immature dendritic cells - Fainaru, Ofer; Almog, Nava; Yung, Chong Wing; Nakai, Kei; Montoya-Zavala, Martin; Abdollahi, Amir; D'Amato, Robert; Ingber, Donald E. (The FASEB journal, 2010)
Dendritic cells (DCs)—immunomodulatory cells that initiate adaptive immune responses—have recently been shown to exert proangiogenic effects when infiltrating the tumor microenvironment. As tumors that escape immune surveillance inhibit DC maturation, we explored whether maturation status determines their ability to promote angiogenesis and whether angiogenesis depends on the presence of DCs. Using mouse xenograft models of human tumors, we show that fast-growing “angiogenic” tumors are infiltrated by a more immature DC population than respective dormant avascular tumors. Accordingly, supplementation of immature DCs, but not mature DCs, enhanced tumor growth. When DCs were mixed with Matrigel and injected subcutaneously into mice, only immature DCs promoted the ingrowth of patent blood vessels. Notably, depletion of DCs in a transgenic mouse model that allows for their conditional ablation completely abrogated basic fibroblast growth factorinduced angiogenesis in Matrigel plugs, and significantly inhibited tumor growth in these mice. Because immature DCs actively promote angiogenesis and tumor growth, whereas DC maturation or ablation suppresses this response, we conclude that angiogenesis is dependent on the presence of immature DCs. Thus, cancer immunotherapies that promote DC maturation may act by both augmenting the host immune response to the tumor and by suppressing tumor angiogenesis.—Fainaru, O., Almog, N., Yung, C. W., Nakai, K., Montoya-Zavala, M., Abollahi, A., D'Amato, R., Ingber, D. E. Tumor growth and angiogenesis are dependent on the presence of immature dendritic cells. FASEB J. 24, 1411-1418 (2010). www.fasebj.org
Online veröffentlicht am 14. Dezember 2009
Gesehen am 07.02.2023